ON METHODS OF FORMATION OF THROUGH TECHNOLOGIES FOR PREPARATION OF AGRICULTURAL RAW MATERIALS AND PRODUCTION OF FUNCTIONAL FOOD PRODUCTS - Shchukin P. O., Krupko A. M., Sukhanov I. V. (Scientific studies and modern education, 2020)
issues of methods of formation of through technologies for preparation of agricultural raw materials and production of functional food products are considered. Some results of such assessment are given.
Keywords: сквозные технологии; сельскохозяйственное сырье; функциональные пищевые продукты; end-to-end technologies; functional food products; agricultural raw materials